Sport medicine and sport science practitioners' experiences of organizational change - Wagstaff, C. R. D.; Gilmore, S.; Thelwell, R. C. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Despite the emergence of and widespread uptake of a growing range of medical and scientific professions in elite sport, such environs present a volatile professional domain characterized by change and unprecedentedly high turnover of personnel. This study explored sport medicine and science practitioners' experiences of organizational change using a longitudinal design over a 2-year period. Specifically, data were collected in three temporally defined phases via 49 semi-structured interviews with 20 sport medics and scientists employed by three organizations competing in the top tiers of English football and cricket. The findings indicated that change occurred over four distinct stages; anticipation and uncertainty, upheaval and realization, integration and experimentation, normalization and learning. Moreover, these data highlight salient emotional, behavioral, and attitudinal experiences of medics and scientists, the existence of poor employment practices, and direct and indirect implications for on-field performance following organizational change. The findings are discussed in line with advances to extant change theory and applied implications for prospective sport medics and scientists, sport organizations, and professional bodies responsible for the training and development of neophyte practitioners.